2015
DOI: 10.5897/jcreo2015.0122
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and survival significance of BAT-25 and BAT-26 instability in breast cancer among Senegalese patients

Abstract: In some tumors, defects in mismatch repair enzymes lead to errors in the replication of simple nucleotide repeat segments. This condition is commonly known as microsatellite instability (MSI) because of the frequent mutations of microsatellite sequences. The primary aim of this study is to evaluate the clinicopathological and survival significance of BAT-25 and BAT-26 instability, in 60 patients with breast cancer. Polymerase chain reaction was used to amplify the following microsatellite repeat loci BAT-25 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…Palombo et al (1995) and Suraweera et al (2002) all nontumor tissues (Pyatt et al, 1999) but so far, the demographic variability of these markers has not been properly reported (Buhard, Suraweera, Lectard, Duval, & Hamelin, 2004). The results in this study point to the high prevalence of BAT-25 in MSI-L/EMAST tumors, but as there are no studies using this panel, the reported incidence for this marker is not comparable with the studies used (IAP1) gene (Mbaye, Ka, Dem, Kane, Sembéne, 2015). In the present study which was conducted in Iran and evaluated MSI based on three quasimonomorphic panel 37.7% of the patients had MSI-L CRCs.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Palombo et al (1995) and Suraweera et al (2002) all nontumor tissues (Pyatt et al, 1999) but so far, the demographic variability of these markers has not been properly reported (Buhard, Suraweera, Lectard, Duval, & Hamelin, 2004). The results in this study point to the high prevalence of BAT-25 in MSI-L/EMAST tumors, but as there are no studies using this panel, the reported incidence for this marker is not comparable with the studies used (IAP1) gene (Mbaye, Ka, Dem, Kane, Sembéne, 2015). In the present study which was conducted in Iran and evaluated MSI based on three quasimonomorphic panel 37.7% of the patients had MSI-L CRCs.…”
Section: Discussioncontrasting
confidence: 59%
“…MSI‐H tumors are associated with a relatively favorable prognosis (Nojadeh, Behrouz Sharif, & Sakhinia, ) that is related to creating numerous neoantigens, which promote infiltration of cytotoxic (CD8 + ) T‐lymphocytes and activated Th1 cells to the tumor microenvironment (Yuza, Nagahashi, Watanabe, Takabe, & Wakai, ). The BAT‐25 locus is a 25(T) repeat identified in intron 16 of the c‐kit proto‐oncogene , BAT‐26 consists of 25 (A) located within the fifth intron of the MSH2 gene, whereas NR‐27 contains a repetition of 27 (A) and is located within the 5′‐untranslated region (UTR) of the inhibitor of apoptosis protein‐1 ( IAP1 ) gene (Mbaye, Ka, Dem, Kane, Sembéne, ). In the present study which was conducted in Iran and evaluated MSI based on three quasimonomorphic panel 37.7% of the patients had MSI‐L CRCs.…”
Section: Discussionmentioning
confidence: 99%